Determination of Vitamin C and Mineral from Spinach (Amaranthus Viridis) Chips for Nutrient Facts - Nazikussabah, Zaharudin; Nurhazwani, Musa; Farahanim, Misni; Siti Maznah, Kabeb (Kulliyah of Nursing International Islamic University Malaysia, 2011)
Spinach is one of the vegetables that contained lots of nutrients and vitamins which is good for human health. Every 100 g of raw green of spinach give 22 kcal of energy. It also contribute nutrient amount of vitamin A, B complex, C, E, K, carotenes, folate, manganese (Mn), calcium (Ca), iron (Fe), protein, potassium (K), carbohydrates and amino acids. Spinach contains anti cancerous food. So it can be used to prevent cancer, control cholesterol level, combat anemia and acidosis, eye problems, high blood pressure and bleeding gums. The objectives of this study are to introduce spinach chips as nutrient food for children and adults, to increase food production based on vegetables and to provide nutrient facts by the determination of Vitamin C, Fe, Ca and K in spinach chips. The study involved the preparation of 100 g spinach (Amaranthus Viridi) chips and the analysis of Vitamin C using AOAC 967.21 test method and also the determination of mineral such as Fe, Ca and K using Atomic Absorption Spectrophotometer (AAS). The results showed that the composition of vitamin C, Fe, Ca and K were 0.31 %; 1.76%; 52.34 % and 45.59 % respectively. The total vitamin and minerals amount of nutrients were 4.8 mg/ 100 g for vitamin C, 814 mg/ kg for Ca, 27.4 mg/ kg for Fe and 709.8 mg/ kg for K. It was found that, spinach contained nutrients value even though it was cooked as chips. High nutrients value especially in vitamin C and minerals provide health benefits to human bodies.